Sesaminol diglucoside isolated from black sesame seed cake and its antioxidant, anti-collagenase and anti-hyaluronidase activities - Nara Nantarat (2020)
© 2020 Elsevier Ltd Sesaminol diglucoside (SDG) was isolated, purified and characterized from defatted sesame seed cake, a by-product of sesame oil extraction. Its antioxidant, anti-hyaluronidase and anti-collagenase activities were investigated. SDG was successfully purified from the methanol fraction using preparative HPLC. The structure was elucidated using 1H and 13C nuclear magnetic resonance spectroscopy and compared with the reference. The in vitro antioxidant activity of SDG was measured using DPPH free radical scavenging and ferric reducing antioxidant power (FRAP) assays. The results showed that SDG was a potential DPPH free radical scavenger with an IC50 value 0.201 ± 0.002 mg/ml and also showed a strong reducing power with FRAP value of 2.18 ± 0.001 mM Fe (II)/g of extract and EC1 value of 0.54 ± 0.001 mg/ml. It also had the highest collagenase inhibition with an IC50 value of 0.26 ± 0.01 mg/ml and hyaluronidase activity of 92.6 ± 0.5% inhibition. Therefore, the SDG could be a promising antioxidant, anti-collagenase and anti-hyaluronidase that could be used for both for neutraceutical and cosmetic applications.